Regional and racial disparities in major amputation rates among medicare beneficiaries with diabetes: a retrospective study in the southeastern USA - Min-Woong Sohn; Anthony McCall; Hyojung Kang; Roger Anderson; Rajesh Balkrishnan; Timothy L McMurry; Meghan B Brennan; Jennifer Mason Lobo; Soyoun Kim (BMJ Publishing Group, 2023)
Objective While rates for non-traumatic lower extremity amputations (LEA) have been declining, concerns exist over disparities. Our objectives are to track major LEA (MLEA) rates over time among Medicare beneficiaries residing in a high diabetes prevalence region in the southeastern USA (the diabetes belt) and surrounding areas.Methods We used Medicare claims files for ~900 000 fee-for-service beneficiaries aged ≥65 years in 2006-2015 to track MLEA rates per 1000 patients with diabetes. We additionally conducted a cross-sectional analysis of data for 2015 to compare regional and racial disparities in major amputation risks after adjusting for demographic, socioeconomic, access-to-care and foot complications and other health factors. The Centers for Disease Control and Prevention defined the diabetes belt as 644 counties across Appalachian and southeastern US counties with high prevalence.Results MLEA rates were 3.9 per 1000 in the Belt compared with 2.8 in the surrounding counties in 2006 and decreased to 2.3 and 1.6 in 2015. Non-Hispanic black patients had 8.5 and 6.9 MLEAs per 1000 in 2006 and 4.8 and 3.5 in 2015 in the Belt and surrounding counties, respectively, while the rates were similar for non-Hispanic white patients in the two areas. Although amputation rates declined rapidly in both areas, non-Hispanic black patients in the Belt consistently had >3 times higher rates than non-Hispanic whites in the Belt. After adjusting for patient demographics, foot complications and healthcare access, non-Hispanic blacks in the Belt had about twice higher odds of MLEAs compared with non-Hispanic whites in the surrounding areas.Discussion Our data show persistent disparities in major amputation rates between the diabetes belt and surrounding counties. Racial disparities were much larger in the Belt. Targeted policies to prevent MLEAs among non-Hispanic black patients are needed to reduce persistent disparities in the Belt.